2020
DOI: 10.1016/j.catena.2019.104411
|View full text |Cite
|
Sign up to set email alerts
|

Holocene fire and vegetation dynamics in the Central Pyrenees (Spain)

Abstract: Fire-vegetation relationships are critical to understand transient mountain ecosystems and their long-term landscape dynamics, which is essential for alpine forest conservation. In this paper we aim to 1) reconstruct the Holocene fire history at high altitudes of the southern Central Pyrenees, 2) add evidence to the debate on fire origin, naturally or anthropogenically produced, 3) determine the importance of fire as a disturbance agent for sub-alpine and alpine vegetation, in comparison with the plant communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 95 publications
(168 reference statements)
0
5
1
Order By: Relevance
“…First, Cyperaceae pollen, reflecting wetland sedges, persisted throughout all periods of study and are evidence of continuation of seasonal wetland conditions in the studied locations from the Late Pleistocene to present (or nearly present) day. Second, increases in Podocarpus and Pinus (tree) taxa in the last 200 years occurred in the auger samples despite evidence for increased concentrations of microcharcoal, which is in general contrast to expected results based on simulated (Keane et al, 2004;D'Odorico et al, 2006;Phelps et al, 2020) and observed (Bakker et al, 2013;Marchant et al, 2018;Leunda et al, 2020) occurrences in ecological research. However, spatially and taxonomically complex ecological simulations challenge simplistic fire-driven forest-to-savannah formation models, demonstrating that fires consume saplings and seedlings that contribute negligibly to biomass (Hanan, 2008).…”
Section: Discussioncontrasting
confidence: 75%
“…First, Cyperaceae pollen, reflecting wetland sedges, persisted throughout all periods of study and are evidence of continuation of seasonal wetland conditions in the studied locations from the Late Pleistocene to present (or nearly present) day. Second, increases in Podocarpus and Pinus (tree) taxa in the last 200 years occurred in the auger samples despite evidence for increased concentrations of microcharcoal, which is in general contrast to expected results based on simulated (Keane et al, 2004;D'Odorico et al, 2006;Phelps et al, 2020) and observed (Bakker et al, 2013;Marchant et al, 2018;Leunda et al, 2020) occurrences in ecological research. However, spatially and taxonomically complex ecological simulations challenge simplistic fire-driven forest-to-savannah formation models, demonstrating that fires consume saplings and seedlings that contribute negligibly to biomass (Hanan, 2008).…”
Section: Discussioncontrasting
confidence: 75%
“…Nevertheless, fire activity increased at ca. 3700 cal BP, indicating a reinforcement of human activities and forest clearing (Leunda et al, 2020).…”
Section: Livestock Management and Landscape Transformation During Pre...mentioning
confidence: 99%
“…This author attributed the rapid deforestation to the need for more summer grasslands as the conquest of the lowlands of the Ebro Depression advanced. Charcoal data from the Basa de la Mora and Marboré sequences from 1250 years BP, and especially during the last 300 years, indicated increasing fire activity during recent centuries (Leunda et al, 2020). In fact, it is impossible to explain the rapid expansion and consolidation of transhumance without a widespread deforestation of the subalpine and upper montane belts, and their transformation into large open landscapes dominated by grasslands.…”
Section: The Late Middle Ages (10th To 15th Centuries): a Key Period ...mentioning
confidence: 99%
“…In the Bereket surroundings, fires appear to have catalyzed a simplification of the vegetation structure and associated increases in soil erosion, pasture expansion, and intensive cultivation (Kaniewski et al, 2008). Leunda et al (2020) use paleofire data from the Central Pyrenees in Spain to show the transition from climate-driven fire regimes in the early-to-mid-Holocene to human-driven landscape change over the last 3700 years. Many similar examples exist throughout Europe.…”
Section: From Fire To Fire Regimesmentioning
confidence: 99%